Nudge in the science and technology policies of China: The experience of Science and Technology Commissioners System in Shenyang - Li, Dan; Wu, Caiyao; Song, Haoqi; Blicharz, Rafał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The Science and Technology Commissioners System (STCS) is an important measure implemented in China to address the bottleneck in rural talent and the underdevelopment of science and technology. This article explores the implementation of the system in rural areas of China, focusing on the behavioural economic perspective of cognitive and behavioural biases in different participants’ decision-making. Shenyang, as a representative base of agricultural production in China, has taken multiple measures to facilitate the implementation of the system. Field interviews revealed that the core challenges in implementing the STCS stem from cognitive biases and from inadequate promotion of behavioural change. These factors contribute to policy rigidity, mismatched service supply and demand, low farmer acceptance, and ineffective supervision and evaluation. Under the framework of nudge theory, this study provides an extensive comparative analysis of international systems, and proposes establishing a ‘Shenyang Science and Technology Commissioners Service Cloud Platform’ and setting up a ‘comprehensive, multi-stakeholder and dynamic’ performance evaluation model.